THE MODERATING ROLE OF NON-DEBT TAX SHIELD ON PROFITABILITY DETERMINANTS - Diva Nur Alifah; Hasan Mukhibad (Kesatuan Press, 2026)
This study examines the effects of intellectual capital, working capital, and leverage on firm profitability, with non-debt tax shield as a moderating variable. Despite the expansion of national infrastructure development, profitability among construction firms remains uneven, as several firms continue to exhibit weak financial performance despite operating under similar industry conditions. This situation suggests that increased project availability does not automatically translate into improved profitability, highlighting potential inefficiencies in the use of internal resources and financial strategies. The analysis is conducted using unbalanced panel data and a Fixed Effects Model. The findings show that intellectual capital and working capital do not have a significant direct effect on profitability, while leverage positively influences profitability. Furthermore, the non-debt tax shield strengthens the relationships between intellectual capital and profitability, as well as between leverage and profitability, but weakens the effect of working capital on profitability. These results highlight the importance of tax-based internal mechanisms in shaping firm profitability.